Controlling Topology within Halogen-Bonded Networks by Varying the Regiochemistry of the Cyclobutane-Based Nodes - Taylor J. Dunning; Daniel K. Unruh; Eric Bosch; Ryan H. Groeneman (Molecules, 2021)
The formation of a pair of extended networks sustained by halogen bonds based upon two regioisomers of a photoproduct, namely rctt-1,3-bis(4-pyridyl)-2,4-bis(phenyl)cyclobutane (ht-PP) and rctt-1,2-bis(4-pyridyl)-3,4-bis(phenyl)cyclobutane (hh-PP), that have varied topology is reported. These networks are held together via I⋯N halogen bonds between the photoproduct and the halogen-bond donor 1,4-diiodoperchlorobenzene (C6I2Cl4). The observed topology in each solid is controlled by the regiochemical position of the halogen-bond accepting 4-pyridyl group. This paper demonstrates the ability to vary the topology of molecular networks by altering the position of the halogen bond acceptor within the cyclobutane-based node.